Causality between Monetary Expansion and the Price Level in India since 1950s - A Re-Examination - Debnath, Sanjib; Mazumder, Ritwik (Journal of Reviews on Global Economics, 2016)
This paper has tested short run causality between broad money supply and whole-sale price index (WPI) in India during 1951-2013 adopting a Toda-Yamamoto (1995) modified Granger causality approach under a VAR environment. Exponentially detrended annual time series data on broad money supply and the whole-sale price index are used for this purpose. Alternative tests for structural breaks reveal significant but dissimilar breaks in the variables. The empirical results are suggestive of a uni-directional causality from broad money supply to WPI. The study further finds that broad money supply and WPI in India have a long-run co-integrating relationship and short run causal relations could hence be expected.